Immune Responses and Efficacy of Brucella Abortus Strain RB51 in Bison After Delivery in a Dry Dart Formulation or by Parenteral Inoculation - Olsen, Steven C.; Boggiatto, Paola M.; Nol, Pauline; McCollum, Matthew P.; Rhyan, Jack C. (Frontiers in Veterinary Science, 2021)
Bison heifer calves (n=32) were randomly assigned to control or vaccination with 1010 colony-forming units of Brucella abortus strain RB51 (RB51) vaccine by single or boostered parenteral delivery, or by surgical implantation of a dry dart formulation (n=8/trt). Serum and/or peripheral blood mononuclear cells (PBMC) were obtained at 0, 4, 8, 13, 16, 21, and 24 wk after initial vaccination and at 0, 4, 8, 12, 15, 22 and 27 wks after booster vaccination to characterize humoral and cellular immune responses to RB51. Bison in both RB51 vaccination treatments demonstrated greater (P<0.05) serum humoral responses when compared to non-vaccinates, with parenteral vaccinates demonstrating greater (P<0.05) responses when compared to mean responses of bison inoculated with the dry dart. Only the booster vaccinated treatment demonstrated greater (P<0.05) humoral responses than control bison in samples collected after re-inoculation. At 4, 8, 12, 16, and 24 wks after initial vaccination, PBMC from parenteral RB51 vaccines demonstrated greater proliferative responses to RB51 when compared to responses of control animals. In comparison, bison inoculated with the RB51 dry dart had greater (P<0.05) proliferative responses only at 8 weeks after inoculation when compared to responses of non-vaccinates. Bison were pasture bred and pregnant animals experimentally challenged in mid-gestation with 107 CFU of B. abortus strain 2308. Bison in parenteral vaccination treatments had reduced (P<0.05) abortions and infection in uterine and fetal samples as compared to non-vaccinated bison, with booster vaccinates tending to have the lowest colonization (CFU/gm) in tissues. In comparison, the dry dart formulation did reduced abortion (P<0.05) but not infection (P>0.05) when compared to non-vaccinated bison. The results of this study reaffirm the efficacy of boostered parenteral vaccination of bison with RB51 in preventing brucellosis. Our data also suggests that the novel dry dart RB51 formulation does not induce sufficient efficacy in bison after a single inoculation.